1999
DOI: 10.2172/754233
|View full text |Cite
|
Sign up to set email alerts
|

EBR-II blanket fuel leaching test using simulated J-13 well water.

Abstract: This paper discusses the results of a pulsed-flow leaching test using simulated J-13 well water leachant. This test was performed on three blanket fiel segments from the ANL-W EBR-11 nuclear reactor which were originally made up of depleted uranium (DU). This experiment was designed to mimic conditions which would exist it upon disposal of this material in a geological repository, it came in direct contact with groundwater. These segments were contained in pressure vessels and maintained at a constant temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similar tests on non-irradiated N Reactor fuel at 25°C (Abrefah et al 2000) are at or lower than the rate forecast by the STP rate law. The 90°C rate datum for uranium metal blanket fuel irradiated to ~30,000 MWD/MTU (Fonnesbeck et al 1998) also is shown in Figure 3.3 and likewise is consistent with the STP rate. Comparable corrosion-rate measurements of non-irradiated EBR-II fuel metal in anoxic liquid water by hydrogen gas generation were conducted at the same 90°C temperature by the same laboratory (Fonnesbeck 2000(Fonnesbeck , 2003.…”
Section: Correspondence Of Irradiated Uranium Metal Corrosion Rates Isupporting
confidence: 72%
See 1 more Smart Citation
“…Similar tests on non-irradiated N Reactor fuel at 25°C (Abrefah et al 2000) are at or lower than the rate forecast by the STP rate law. The 90°C rate datum for uranium metal blanket fuel irradiated to ~30,000 MWD/MTU (Fonnesbeck et al 1998) also is shown in Figure 3.3 and likewise is consistent with the STP rate. Comparable corrosion-rate measurements of non-irradiated EBR-II fuel metal in anoxic liquid water by hydrogen gas generation were conducted at the same 90°C temperature by the same laboratory (Fonnesbeck 2000(Fonnesbeck , 2003.…”
Section: Correspondence Of Irradiated Uranium Metal Corrosion Rates Isupporting
confidence: 72%
“…Overall, the paired findings for the irradiated and non-irradiated N Reactor fuel at 25°C Einziger 1998 andAbrefah et al 2000, respectively) and irradiated and non-irradiated EBR-II fuel at 90°C (Fonnesbeck et al 1998and Fonnesbeck 2000, 2003 show irradiation to increase rates. However, the effects of irradiated fuel crumbling or increased surface area were not investigated.…”
Section: Correspondence Of Irradiated Uranium Metal Corrosion Rates Imentioning
confidence: 89%
“…In immersion oxidation tests performed on irradiated uranium, around 10% uranium hydride was observed in the reaction products of some of the samples that were not completely oxidized. 75 Since uranium hydride is an intermediate product that oxidizes to UO 2 , a transient amount of residual UH 3 is expected to form while the U metal is still reacting and if the UH 3 oxidation rate is less than the U metal oxidation rate, as has been reported. 80,81 In some studies, the presence of hydride has been speculated to increase the reaction rate of uranium metal oxidation.…”
Section: Uranium-hydride Effects On Uranium Metal Oxidationmentioning
confidence: 88%
“…The similarity between oxidation rates of KW SNF and U metal is also consistent with dissolution rates of irradiated uranium metal fuel reported by Gray and Einziger at PNNL and Fonnesbeck at Argonne National Laboratory-West (ANL-W). 74,75 The effects of irradiation on uranium metal oxidation are summarized as follows. Irradiation does not increase the intrinsic oxidation rate of uranium metal.…”
Section: Irradiation Effects On Uranium Metal Oxidationmentioning
confidence: 99%
“…The corrosion of the highly irradiated EBR-II blanket fuel was tested in closed vessels with initially aerated simulated groundwater and air cover gas (Fonnesbeck et al 1998). The vessels were opened weekly for sampling, fresh aerated water was added, and the vessels were reclosed.…”
Section: Uranium Metal Corrosion Rates In Oxic Liquid Watermentioning
confidence: 99%